Changes in quantity and quality of organic matter in soil after application of poultry litter and poultry litter biochar—5-year field experiment - Jarosz, Renata; Mierzwa-Hersztek, Monika; Gondek, Krzysztof; Kopeć, Michał; Lošák, Tomáš; Marcińska-Mazur, Lidia (Biomass conversion and biorefinery, 2022)
Changes of the addition of poultry litter (PL) and poultry litter biochar (PLB) on quantitative and qualitative humus parameters in loamy sand were estimated during the 5-year study period. The following properties were determined in soil: pH, total carbon (Ctotal), total nitrogen (Ntotal), humic and fulvic acids, extracted carbon, and non-hydrolysing carbon. Additionally, light absorbance in the solutions of humic acids was computed at the wavelength of 280, 465, and 665 nm. It was demonstrated that organic matter mineralisation was most intense in soil with the addition of PL, causing significant quantitative and qualitative changes in humus compounds in soil. A slower rate of organic matter mineralisation was observed in soil amended with PLB, especially in a dose of 5.0 t ha −1 , which indicated the long-term effect of this material on improving soil properties. Spectrophotometric indexes for the solution of humic acids also showed that PLB had a more favourable effect on the structure durability and lower mobility of humic acid carbon compared with PL. The application of PL and PLB significantly increased the non-hydrolysing carbon content in soil, indicating greater stabilisation of humus compounds and, at the same time, lower CO 2 emissions. It was found that the addition of organic materials to soil significantly increased the soil organic carbon contents. Our study has shown that the identification of changes that may occur in the quantitative and qualitative composition of soil humus after the application of PLB may be helpful in determining the appropriate biochar dose. Graphical abstract